Cherubism and anaesthesia - E. Gentili, Marc; Levreil, Edwige; Bedhet, Nicolas (Anestezjologia Intensywna Terapia, 2021)
Respiratory complications are one of the main problems in paediatric anaesthesia. Cherubism is a rare familial disease causing enlargement of the mandible that may be associated with difficult intubation [1, 2]. A 5-year-old, 20 kg, ASA 1, healthy girl was evaluated for anaesthesia requested for the removal of mandibular lesions (Figure 1). She had a positive family history of cherubism; her father and cousins were affected. Radiographically, the lesions demonstrated multilocular, expansile radiolucencies with mandibular enlargement. The preoperative examination was unremarkable: normal neck flexion, no trismus, and a Mallampati score of 1. A venous catheter was inserted peripherally under N2O inhalation and transdermic lidocaine and prilocaine patch. The general anaesthesia combined sevoflurane and IV sufentanil. Nasotracheal intubation under direct laryngoscopy was uneventful. After the surgery, which lasted 120 minutes, she was admitted to the post anaesthesia care unit for 1 night and discharged the next day without any sequelae.